Altered Lipid Tumor Environment and Its Potential Effects on NKT Cell Function in Tumor Immunity - Tiwary, Shweta; Berzofsky, Jay A.; Terabe, Masaki (Frontiers in Immunology, 2019)
Natural killer T (NKT) cells are CD1d restricted T cells that mostly recognize lipid antigens. These cells share characteristics with both adaptive and innate immune cells and have multiple immunoregulatory roles. In a manner similar to innate immune cells, they respond quickly to stimuli and secrete large amounts of cytokines, amplifying and modulating the immune response. As T cells, they express T cell receptors (TCRs) and respond in an antigen-specific manner like conventional T cells. There are at least two subtypes of NKT cells, type I and type II, that differ in the nature of their TCR, either semi-invariant (type I) or diverse (type II). The two sub-types generally have opposing functions in tumor immunity, with type I promoting and type II suppressing tumor immunity, and they cross-regulate each other, forming an immunoregulatory axis. The tumor has multiple mechanisms by which it can evade immune-surveillance. One such mechanism involves alteration in tumor lipid repertoire and accumulation of lipids and fatty acids that favor tumor growth and evade anti-tumor immunity. Since NKT cells mostly recognize lipid antigens, an altered tumor lipid metabolic profile will also alter the repertoire of lipid antigens that can potentially affect their immune-modulatory function. In this review, we will explore the effects of alterations in the lipid metabolites on tumor growth, antigen cross-presentation, and overall effect on anti-tumor immunity, especially in the context of NKT cells.